Effects of ternary mixtures of propane-butane-hydrogen and different liquid fuels on the performance specifications of a spark ignition engine - Gonca, Guven; Genc, Ibrahim (TAYLOR & FRANCIS INC, 2022)
This study reports the influences of ternary fuel mixtures consisting of liquefied propane-butane-hydrogen as additives and methanol, ethanol, iso-octane, hexane, benzene, toluene and gasoline as primary fuels on the performance specifications such as variation of power, thermal efficiency, exergy efficiency and NO of a spark ignition (SI) engine by using a combustion model. Mass ratio of one kind of gas fuels has been kept constant as 50%, mass ratios of other two kinds of gas fuels have been ranged from 10 to 50%. Hydrogen addition to mixtures has parabolically affected the variation of performance characteristics. However, they have been linearly affected by propane and butane additions. Increment and reduction trends of the performance characteristics have changed depending on liquid fuel kinds. Maximum power output is observed with 50% mixture of toluene, minimum power output is revealed with 50% mixture of methanol, maximum values of thermal and exergy efficiencies are acquired with 50% butane-30%-toluene-20% hydrogen, 50% propane-20% methanol-30% hydrogen mixture provides minimum thermal efficiency, 50% propane-30% methanol-20% hydrogen mixture provides minimum exergy efficiency. The maximum NO is observed with 50% mixture of benzene. Minimum NO is acquired with 50% mixture of propane. The maximum values of power, thermal efficiency, exergy efficiency and NO formation have been obtained as 14.16 kW, 34.37%, 33.49% and 5.78E-7 mol/cm 3 respectively. Their minimum values are 6.69 kW, 28.01%, 27.54% and 3.61E-9 mol/cm 3, respectively. The results revealed that ternary fuel mixtures considerably affect the performance specifications and NO releasement of the SI engine. An Artificial Neural Network (ANN) model of the engine is constructed for a wider view. The results of the presented study can be used to assess the effects of ternary fuel mixtures on the performance characteristics and NO formation of an SI engine.
Keywords: Ternary fuel mixtures; spark ignition engine; gas fuels; liquid fuels; engine performance; NO emission; DIRECT-INJECTION; DIESEL-ENGINE; SI ENGINE; STEAM INJECTION; COMBUSTION PERFORMANCE; ROTARY ENGINE; GASOLINE; EMISSIONS; PARAMETERS; ENRICHMENT; Energy & Fuels; Engineering; Environmental Sciences & Ecology